THE IMPROVEMENT OF KnK KOFFEE RESOURCES’S FINANCIAL REPORTING SYSTEM - Sari, Maylia Pramono; Ardiansari, Anindya; Raharja, Surya (2020, 2020)
The 4.0 Industrial Revolution aims is a efficiency so as not to be affected by change and able to turn it into an opportunity, the perpetrators of micro-medium enterprises (MSMES) must start the transformation process into the digital era. The activities of community services conducted by Community Services Team of (PPM Unnes) and (PPM Undip) with the target audience of one Micro Small and Medium enterprises (MSMES) in the city of Semarang, namely Knk Koffee Resources. This home industry processing coffee is the stockist of 60 (supplier 75%) coffee shop in Semarang, with an average turnover of 100 million per month. Responding to the phenomenon of Gap (KnK Koffe Resources has not yet had financial reports and uses manual bookkeeping in the digital age) and theoritical Gap (signaling theory and cost benefit analysis), then the purpose of this PPM activity to provide reinforcement to PPM Program by providing assistance with solutions to the problems faced. KnK Koffee Resources does not yet have a financial statement, so far only relies on the recap of billing and sales result notes. Recognition from the owner that it is still difficult to make decision making when relying solely on bookkeeping reports that have been owned. Therefore, this PPM activity is indispensable to improve the financial reporting system of KnK Koffee Resources in the form of socialization, training and mentoring with the provision of materials (lectures and simulation practices) related to the preparation of Financial Statement based on accounting software (LAMikro). PPM results show that there is an increase of the owners and administrative employees knowledge and skills in conducting Financial Management, Financial Statement preparation, increased sales turnover (73 million for 5 months, strat from Mei to October 2019), community welfare increased and facilitate funding for business expansion. Semarang Mayor is very supportive, give positive appreciation and make the example of Koffee Resources KnK this as a coffee processing home industry that has successfully penetrated business penetration, not only dwell in the market of Semarang only. With the improvement of Financial Reporting System to KnK Koffee Resources triggers the creation of a young business ecosystem of startups in Semarang. Keywords— Accounting Software, Financial Reporting System, SMEs KnK Koffee Resources